Pre-Sale Strategy for Fresh Agricultural Products Under the Consideration of Logistics Services - Xiuping Han (IEEE Access, 2021)
Purpose – There is particularly high loss rate for fresh agricultural products (FAP) in the operation of actual supply chain and the development of FAP e-commerce is hindered to some extent. The purpose of this paper is to solve the customer to business (C2B) pre-sale problems of FAP supply chain, in which a third-party logistics service provider (TPLSP) participates in decision-making, to increase the income of each member and to ensure that consumers can obtain the freshest FAP. Design/methodology/approach – This paper considers the C2B pre-sale strategies as a three-echelon fresh FAP supply chain, where the supplier pre-sell products through the online retailers. The market demand in the online channel depends on the retailer’s service level, the pre-sale discount rate and the logistics service efforts of TPLSP. Findings–Stackelberg game method is adopted to study the equilibrium strategies of a supplier-led FAP supply chain under centralized and decentralized decision-making with the existence of a TPLSP, and the optimal pre-sale discount rate, the optimal online service level and the optimal logistics service price provided by TPLSP in the two decision modes are obtained, as well as the optimal profits of the supply chain and each member. Practical implications – The paper provides a practical guideline to managers in fresh products industry in terms of how to cooperate with other supply chain members so as to maximize total profit and to achieve Pareto improvement, and at the meantime, to supply the freshest and safest products to the target market under e-commerce environment. Originality/value – For the e-commerce supply chains with TPLSP participates in decision-making, there are few studies which considers the FAP pre-sale, especially consider the case that the market demand for FAP is affected by freshness and online selling price per unit simultaneously. This paper takes these cases into account, establishes the corresponding mathematical model, and designs a coordination mechanisms.